Relative potency of ketamine and S(+)-ketamine in dogs - Duque, J. C.; Oleskovicz, N.; Guirro, E. C. B. P.; Valadao, C. A. A. [UNESP]; Soares, V. E. [UNESP] (Wiley-Blackwell, 2008)
The aim of this study was to determine the relative potency of racemic ketamine and S(+)-ketamine for the hypnotic effect and to evaluate the clinical anesthesia produced by equianesthetic doses of these two substances in dogs. One hundred and eight dogs were allocated in groups R2, R2.5, R3, R6, R9, R12, S2, S2.5, S3, S6, S9, and S12, to receive by intravenous route 2, 2.5, 3, 6, 9, and 12 mg/kg of ketamine or S(+)-ketamine, respectively. A dose-effect curve was drawn with the dose logarithm and the percentage of dogs that presented hypnosis in each group. The curve was used to obtain a linear regression, to determine the effective doses 100 and the potency relationship. In another experimental phase, eight groups of five dogs received 3, 6, 9 and 12 mg/kg of ketamine or S(+)-ketamine to evaluate the periods of latency, hypnosis, and total recovery. The times in which the dogs reached the sternal position, attempted to stand up for the first time, recovered the standing position, and started to walk were also recorded. The hypnotic dose for ketamine was 9.82 +/- 3.02 (6.86-16.5) mg/kg and for S(+)-ketamine was 7.76 +/- 2.17 (5.86-11.5) mg/kg. The time of hypnosis was longer in R3 and the first attempt to stand up occurred early in R6 when compared with S3 and S6 respectively. When R9 (100% of hypnosis with ketamine) and S6 [100% of hypnosis with S(+)-ketamine] were compared (1:1.5 ratio), the time to sternal position (12 +/- 2.5 and 20.2 +/- 5.6 min respectively) and the total recovery time (45 +/- 5.5 and 60.2 +/- 5.2 min respectively) were significantly shorter with S(+)-ketamine. It was concluded that the potency ratio between ketamine and S(+)-ketamine in dogs is smaller than the one reported in other species, and that the dose obtained after a reduction of 50%, as usually performed in humans, would not be enough to obtain equianesthetic effects in dogs.